Management of Lime in Steel - Sanjeev Manocha; François Ponchon (Metals, 2018)
The EU28 total lime demand in 2017 was estimated at about 20 million tons, out of which about 40% are consumed in the iron and steel industry. Steel remains the major consumer after environment and construction. The lime industry is quite mature and consolidated in developed countries, with enough reserves and production to serve regional markets while being fragmented in developing nations where steel producers rely on local sourcing. There is relatively very little trade for lime worldwide. Lime has a critical role at different steps of the steelmaking process, and especially to make a good slag facilitating the removal of sulphur and phosphorus, and for providing a safer platform to withstand high intensity arc plasma in the electric arc furnace (EAF), and violent reactions in the basic oxygen furnace (BOF). Lime quality and quantity has a direct effect on slag quality, which affects metallurgical results, refractory life, liquid metal yield, and productivity, and therefore the total cost of the steel production. In this paper, we present the importance of careful selection in the limestone and calcination process, which influences critical lime quality characteristics. We shall further elaborate on the impact of lime characteristics in the optimization of the steelmaking process, metallurgical benefits, overall cost impact, potential savings, and environmental benefits.